Developing assistive technology to support reminiscence therapy: a user-centered study - Alarcão, Soraia M.; Santana, André; Vieites, Bruna; Neves, Pedro; Alves, Raúl; Maruta, Carolina; Fonseca, Manuel J. (Frontiers in Medicine, 2025)
Caregivers are one of the main pillars in adopting digital technologies for reminiscence therapy, as they are responsible for its administration. Despite their comprehensive understanding of the needs and difficulties associated with the therapy, their perspective has not been fully considered in existing technological solutions. To mitigate this gap, we followed a user-centered design approach, using a sequential process that included worldwide web-based surveys, follow-up interviews, and focus groups to inform the development of novel assistive technological solutions focused on the real needs of caregivers. A total of 713 informal and 67 formal caregivers participated in our study. Our findings reveal that caregivers are overburdened with the amount of work they have daily; thus, mechanisms that could help them manage all the tasks involved in therapy (e.g., creating sessions, gathering feedback for further consultation) would help to reduce their workload while potentially improving the quality of therapy sessions. Caregivers also want to be able to easily leverage emotions during therapy to personalize and diversify sessions over time, thus preventing aggression or agitation in people with dementia. As a result of our study, we propose a list of functional requirements gathered for both formal and informal caregivers and the corresponding expected primary and secondary outcomes, such as improvement of the cognitive function of people with dementia, reduction of caregivers' stress and burden, and reduction of behavioral symptoms of people with dementia. We also present the resulting architecture of the KeepsakeBox prototype, which allows creating, managing, and delivering personalized reminiscence therapy sessions to people with dementia, which can be used as a basis for the development of future technological solutions for reminiscence therapy.